Preparation method of anti-ultraviolet aging thermal insulation slurry
Patent Information
- Application Number
- CN202510066219.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-16
- Publication Date
- 2025-04-25
Smart Images

Figure BDA0005244333850000071
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of cosmetics, and in particular to a method for preparing an anti-ultraviolet aging thermal insulation slurry. Background Art
[0002] In recent years, with the rise in global temperatures, skin diseases caused by sunlight exposure have become more and more serious. Therefore, sun protection has become a mainstream topic. Nowadays, sunscreen cosmetics with a single sunscreen function can no longer meet consumer demand. The development of multi-functional sunscreen products has become an urgent problem that major cosmetics companies need to solve.
[0003] Superhydrophobic SiO2 aerogel is a nanoporous material with low density, low thermal conductivity, high specific surface area and high porosity. Therefore, it has excellent thermal insulation properties and is widely used in cosmetics, construction, aerospace, energy storage, new energy electric vehicles and other fields. Nano CeO2 is widely used in sunscreen cosmetics due to its good stability, excellent UV shielding effect and long time effectiveness. Fluorphlogopite has better elasticity, toughness, insulation, high temperature resistance, acid and alkali resistance, corrosion resistance and adhesion than natural mica, so it is widely used in various fields. When they are mixed, their advantages can be brought into play to make multifunctional sunscreen products. However, due to the easy agglomeration of particles, it is difficult to disperse evenly in the solution and the poor stability have always existed, which greatly limits their effectiveness. Moreover, the powder is very easy to cause dust pollution when used directly. The nanotoxicity produced by nanoparticles will also pose a serious threat to human health. For this reason, we propose a preparation method of anti-UV aging thermal insulation slurry. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing an anti-ultraviolet aging thermal insulation slurry to solve the problems raised in the above background technology.
[0005] To achieve the above object, the present invention provides the following technical solution: a method for preparing an anti-ultraviolet aging thermal insulation slurry, comprising the following steps:
[0006] (1) Acidification treatment: under the condition of stirring at a temperature of 60-90°C, add an acidic solution with a concentration of 2-4 mol / L to a mixed aqueous solution of nano-CeO2 and fluorphlogopite with a solid content of 10%-30% until the pH value of the system reaches 1-4, stop adding the acidic solution, keep stirring for 2-6 hours, filter and wash with deionized water until the conductivity is ≤100μs / cm, dry at 80°C, grind, and obtain an acid-treated mixed powder;
[0007] (2) Slurry preparation: The mixed powder and super-hydrophobic SiO2 aerogel particles are sequentially added to silicone oil, pre-dispersed at 500 rpm for 10 min using a dispersing disk of a disperser, and then the dispersant is added dropwise while stirring. After the addition is complete, the grinding wheel is replaced and zirconium oxide balls are added. After continuing to disperse at 4500 rpm for 1 h, the zirconium oxide balls are filtered out to obtain an anti-ultraviolet aging thermal insulation slurry.
[0008] Preferably, the acidic solution is any one of HCL, H2SO4, HNO3 or a mixture of several thereof.
[0009] Preferably, the particle size of the nano-CeO2 particles is 20-50 nm, the particle size of the fluorphlogopite particles is 1-3 μm, and the nano-CeO2 particles and the fluorphlogopite particles are mixed in a mass ratio of 1:0.1-0.5.
[0010] Preferably, the super hydrophobic SiO2 aerogel particles have a particle size of 100-300 nm.
[0011] Preferably, the weight portion of the mixed powder is 5-20 parts, the weight portion of the superhydrophobic SiO2 aerogel is 5-20 parts, the weight portion of the silicone oil is 60-90 parts, and the weight portion of the dispersant is 1-5 parts.
[0012] Preferably, the silicone oil is any one of dimethyl silicone oil, cyclopentadecasiloxane silicone oil or phenyl polytrimethicone silicone oil.
[0013] Preferably, the dispersant is any one of PEG-10 polydimethylsiloxane, PEG-9 polydimethylsiloxyethyl polydimethylsiloxane, octyldodecanol stearoyloxystearate or PEG-11 methyl ether polydimethylsiloxane.
[0014] Preferably, the particle size of the zirconia balls is 0.3 mm, and the weight of the added zirconia balls is 1.5 times the total weight of the dispersion slurry.
[0015] Compared with the prior art, the present invention has the following beneficial effects:
[0016] 1. The present invention uses super-hydrophobic SiO2 aerogel, nano-CeO2 and fluorphlogopite in combination. On the one hand, the excellent high temperature resistance of fluorphlogopite can be matched with the thermal insulation performance of super-hydrophobic SiO2 aerogel to produce a gain effect. On the other hand, fluorphlogopite itself has the ability to resist ultraviolet rays. After being compounded with nano-CeO2, it can play a synergistic role in enhancing the ability to resist ultraviolet aging.
[0017] 2. The present invention uses fluorphlogopite, which reduces the amount of super-hydrophobic SiO2 aerogel without reducing the thermal insulation effect, saving costs. At the same time, after acid treatment, fluorphlogopite can serve as a carrier of nano-CeO2 and reduce the agglomeration of nanoparticles.
[0018] 3. The present invention prepares the particles into a dispersion slurry, which on the one hand avoids dust pollution and nano-toxicity problems generated during use, and on the other hand can break up the agglomerated particles through grinding and stirring with zirconium oxide balls. The addition of dispersant allows the particles to be evenly and stably dispersed in the silicone oil, greatly improving the various properties of the dispersion slurry.
[0019] 4. The dispersion slurry prepared by the present invention is added to cosmetics and applied on the skin. It is non-toxic, harmless, safe and stable. While resisting ultraviolet rays, it isolates the heat generated by sunlight to ensure that the body is comfortable and cool. DETAILED DESCRIPTION
[0020] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0021] Example 1
[0022] A method for preparing an anti-ultraviolet aging thermal insulation slurry comprises the following steps:
[0023] (1) Under stirring at 90° C., a 2 mol / L HCL solution was added to a mixed aqueous solution of nano-CeO2 and fluorphlogopite with a solid content of 30% (nano-CeO2 particles and fluorphlogopite particles were mixed at a mass ratio of 1:0.5) until the pH value of the system reached 1, and then the addition of the acidic solution was stopped. After stirring at this temperature for 6 hours, the mixture was filtered and washed with deionized water until the conductivity was ≤100 μs / cm, and then dried at 80° C. and ground to obtain an acid-treated mixed powder;
[0024] (2) 20 parts of the mixed powder and 10 parts of super-hydrophobic SiO2 aerogel particles were added to 67 parts of dimethyl silicone oil in sequence, and pre-dispersed at 500 rpm for 10 minutes using a dispersing disk of a disperser. Then, 3 parts of PEG-10 polydimethylsiloxane were added dropwise while stirring. After the addition was completed, the grinding wheel was replaced, and zirconium oxide balls with a particle size of 0.3 mm and 1.5 times the weight of the dispersion slurry were added. After continuing to disperse at a speed of 4500 rpm for 1 hour, the zirconium oxide balls were filtered out to obtain an anti-ultraviolet aging thermal insulation slurry.
[0025] Example 2
[0026] A method for preparing an anti-ultraviolet aging thermal insulation slurry comprises the following steps:
[0027] (1) Under stirring conditions at a temperature of 60° C., a 4 mol / L H2SO4 solution was added to a 10% solid content nano-CeO2 and fluorphlogopite mixed aqueous solution (nano-CeO2 particles and fluorphlogopite particles were mixed at a mass ratio of 1:0.1) until the pH value of the system reached 4, then the addition of the acidic solution was stopped, and after stirring at this temperature for 2 h, the mixture was filtered and washed with deionized water until the conductivity was ≤100 μs / cm, and then dried at 80° C. and ground to obtain an acid-treated mixed powder;
[0028] (2) 10 parts of the mixed powder and 20 parts of super-hydrophobic SiO2 aerogel particles are added to 65 parts of cyclopentadecasiloxane silicone oil in sequence, and pre-dispersed at 500 rpm for 10 minutes using a dispersing disk of a dispersing mixer, followed by dropwise addition of 5 parts of PEG-11 methyl ether polydimethylsiloxane while stirring. After the addition is complete, the grinding wheel is replaced, and zirconium oxide balls with a particle size of 0.3 mm and 1.5 times the weight of the dispersion slurry are added. After continuing to disperse at a speed of 4500 rpm for 1 hour, the zirconium oxide balls are filtered out to obtain an anti-ultraviolet aging thermal insulation slurry.
[0029] Example 3
[0030] A method for preparing an anti-ultraviolet aging thermal insulation slurry comprises the following steps:
[0031] (1) Under stirring at 80° C., a 3 mol / L HNO3 solution was added to a 10% solid content nano-CeO2 and fluorphlogopite mixed aqueous solution (nano-CeO2 particles and fluorphlogopite particles were mixed at a mass ratio of 1:0.3) until the pH value of the system reached 2, then the addition of the acidic solution was stopped, and after stirring at this temperature for 4 h, the mixture was filtered and washed with deionized water until the conductivity was ≤100 μs / cm, and dried at 80° C. and ground to obtain an acid-treated mixed powder;
[0032] (2) 15 parts of the mixed powder and 10 parts of the super-hydrophobic SiO2 aerogel particles are sequentially added to 71 parts of phenyl polytrimethylsiloxane silicone oil, and pre-dispersed at 500 rpm for 10 min using a dispersing disk of a dispersing mixer, followed by dropwise addition of 4 parts of octyldodecanol stearyloxystearate while stirring. After the addition is complete, the grinding wheel is replaced, and zirconium oxide balls with a particle size of 0.3 mm and 1.5 times the weight of the dispersion slurry are added. After continuing to disperse at a speed of 4500 rpm for 1 h, the zirconium oxide balls are filtered out to obtain an anti-ultraviolet aging thermal insulation slurry.
[0033] Comparative Example 1
[0034] (1) Under the condition of stirring at a temperature of 90° C., a 2 mol / L HCL solution was added to a nano CeO2 aqueous solution having a solid content of 30% until the pH value of the system reached 1, and then the addition of the acidic solution was stopped. After stirring at this temperature for 6 hours, the mixture was filtered and washed with deionized water until the conductivity was ≤100 μs / cm, and then dried at 80° C. and ground to obtain an acid-treated nano CeO2 powder;
[0035] (2) 20 parts of nano-CeO2 powder and 10 parts of super-hydrophobic SiO2 aerogel particles were added to 67 parts of dimethyl silicone oil in sequence, and pre-dispersed at 500 rpm for 10 minutes using a dispersing disk of a disperser. Then, 3 parts of PEG-10 polydimethylsiloxane were added dropwise while stirring. After the addition was completed, the grinding wheel was replaced, and zirconium oxide balls with a particle size of 0.3 mm and 1.5 times the weight of the dispersion slurry were added. After continuing to disperse at a speed of 4500 rpm for 1 hour, the zirconium oxide balls were filtered out to obtain an anti-ultraviolet aging thermal insulation slurry.
[0036] Comparative Example 2
[0037] (1) Under stirring at 90° C., a 2 mol / L HCL solution was added to a mixed aqueous solution of nano-CeO2 and fluorphlogopite with a solid content of 30% (nano-CeO2 particles and fluorphlogopite particles were mixed at a mass ratio of 1:0.5) until the pH value of the system reached 1, and then the addition of the acidic solution was stopped. After stirring at this temperature for 6 hours, the mixture was filtered and washed with deionized water until the conductivity was ≤100 μs / cm, and then dried at 80° C. and ground to obtain an acid-treated mixed powder;
[0038] (2) Add 20 parts of the mixed powder to 77 parts of dimethyl silicone oil, pre-disperse at 500 rpm for 10 minutes using a dispersing disk of a disperser, then drop 3 parts of PEG-10 polydimethylsiloxane while stirring. After the addition is complete, replace the grinding wheel, add zirconium oxide balls with a particle size of 0.3 mm and 1.5 times the weight of the dispersion slurry, continue to disperse at a speed of 4500 rpm for 1 hour, filter out the zirconium oxide balls, and obtain an anti-ultraviolet aging thermal insulation slurry.
[0039] Comparative Example 3
[0040] (1) Under the condition of stirring at a temperature of 90° C., a 2 mol / L HCL solution is added to a 30% solid content fluorphlogopite aqueous solution until the pH value of the system reaches 1, and then the addition of the acidic solution is stopped. After stirring at this temperature for 6 hours, the mixture is filtered and washed with deionized water until the conductivity is ≤100 μs / cm, and then dried at 80° C. and ground to obtain an acid-treated fluorphlogopite powder;
[0041] (2) 20 parts of fluorphlogopite powder and 10 parts of superhydrophobic SiO2 aerogel particles are added to 67 parts of dimethyl silicone oil in sequence, and pre-dispersed at 500 rpm for 10 minutes using a dispersing disk of a disperser. Then, 3 parts of PEG-10 polydimethylsiloxane are added dropwise while stirring. After the addition is complete, the grinding wheel is replaced, and zirconium oxide balls with a particle size of 0.3 mm and 1.5 times the weight of the dispersion slurry are added. After continuing to disperse at a speed of 4500 rpm for 1 hour, the zirconium oxide balls are filtered out to obtain an anti-ultraviolet aging thermal insulation slurry.
[0042] Comparative Example 4
[0043] (1) Under stirring at 90° C., a 2 mol / L HCL solution was added to a mixed aqueous solution of nano-CeO2 and fluorphlogopite with a solid content of 30% (nano-CeO2 particles and fluorphlogopite particles were mixed at a mass ratio of 1:0.5) until the pH value of the system reached 1, and then the addition of the acidic solution was stopped. After stirring at this temperature for 6 hours, the mixture was filtered and washed with deionized water until the conductivity was ≤100 μs / cm, and then dried at 80° C. and ground to obtain an acid-treated mixed powder;
[0044] (2) 20 parts of the mixed powder and 10 parts of the super-hydrophobic SiO2 aerogel particles were added to 67 parts of dimethyl silicone oil in sequence, and pre-dispersed at 500 rpm for 10 min using a dispersing disk of a disperser. The grinding wheel was replaced, and zirconium oxide balls with a particle size of 0.3 mm and 1.5 times the weight of the dispersion slurry were added. After continuing to disperse at a speed of 4500 rpm for 1 hour, the zirconium oxide balls were filtered out to obtain an anti-ultraviolet aging thermal insulation slurry.
[0045] Comparative Example 5
[0046] (1) Under stirring at 90° C., a 2 mol / L HCL solution was added to a mixed aqueous solution of nano-CeO2 and fluorphlogopite with a solid content of 30% (nano-CeO2 particles and fluorphlogopite particles were mixed at a mass ratio of 1:0.5) until the pH value of the system reached 1, and then the addition of the acidic solution was stopped. After stirring at this temperature for 6 hours, the mixture was filtered and washed with deionized water until the conductivity was ≤100 μs / cm, and then dried at 80° C. and ground to obtain an acid-treated mixed powder;
[0047] (2) 20 parts of the mixed powder and 10 parts of super-hydrophobic SiO2 aerogel particles were added to 67 parts of dimethyl silicone oil in sequence, and pre-dispersed at 500 rpm for 10 minutes using a dispersing disk of a disperser, and then 3 parts of PEG-10 polydimethylsiloxane were added dropwise while stirring. After the addition was completed, the grinding wheel was replaced, and the dispersion was continued at 4500 rpm for 1 hour, and the zirconium oxide balls were filtered out to obtain an anti-ultraviolet aging thermal insulation slurry.
[0048] The dispersion slurries prepared in the examples and comparative examples were ultrasonically dispersed in anhydrous ethanol to prepare 40 ppm dispersions, and then their absorbances were measured using an ultraviolet-visible spectrophotometer (UV3600, Shimadzu Corporation, Japan) using a quartz cuvette with an optical path of 1 cm and anhydrous ethanol as a reference. 308 and A 360 It indicates the ability of the dispersion slurry to resist ultraviolet rays. The larger the two values are, the stronger its ability to resist ultraviolet rays is. The measurement results are shown in Table 1 below.
[0049] Table 1 Absorbance of different dispersion slurries
[0050]
[0051] According to the data in Table 1, it can be seen from Example 1, Comparative Example 4 and Comparative Example 5 that the dispersion slurry to which dispersant and zirconia balls are added during production has a stronger ability to resist ultraviolet rays, and from Comparative Example 1, the dispersion slurry to which fluorphlogopite is added has a better ability to resist ultraviolet rays. It can be seen that the dispersion slurry particles prepared by the present invention have good dispersion stability and excellent ultraviolet resistance.
[0052] The dispersion slurry prepared in the embodiment and the comparative example was ground and mixed with vaseline to form a simulated sunscreen with a solid content of 10%. The simulated sunscreen of the same mass was evenly applied on a 50*50 mm glass plate and placed on a heating table at 100°C. After 20 minutes, the temperature of the other side (cold side) was tested and the temperature difference was calculated. The larger the temperature difference, the better the thermal insulation performance. The measurement results are shown in Table 2 below.
[0053] Table 2 Thermal insulation properties of different dispersion slurries
[0054] sample Hot surface temperature / ℃ Cold surface temperature / ℃ Temperature difference / ℃ Example 1 100 38 62 Example 2 100 36 64 Example 3 100 41 59 Comparative Example 1 100 46 54 Comparative Example 2 100 60 40 Comparative Example 3 100 40 60 Comparative Example 4 100 48 52 Comparative Example 5 100 51 49
[0055] According to the data in Table 2, it can be seen from the embodiment and comparative example 2 that the sample with the addition of superhydrophobic SiO2 aerogel has excellent thermal insulation performance, and from comparative example 1, the addition of fluorophlogopite makes the thermal insulation performance of the dispersion slurry better. It can be seen that the dispersion slurry prepared by the present invention has excellent thermal insulation ability.
[0056] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing an anti-ultraviolet aging thermal insulation slurry, characterized in that: The following steps are involved: (1) Acidification treatment: under the condition of stirring at a temperature of 60-90°C, add an acidic solution with a concentration of 2-4 mol / L to a mixed aqueous solution of nano-CeO2 and fluorphlogopite with a solid content of 10%-30% until the pH value of the system reaches 1-4, stop adding the acidic solution, keep stirring for 2-6 hours, filter and wash with deionized water until the conductivity is ≤100μs / cm, dry at 80°C, grind, and obtain an acid-treated mixed powder; (2) Slurry preparation: The mixed powder and super-hydrophobic SiO2 aerogel particles are sequentially added to silicone oil, pre-dispersed at 500 rpm for 10 min using a dispersing disk of a disperser, and then the dispersant is added dropwise while stirring. After the addition is complete, the grinding wheel is replaced and zirconium oxide balls are added. After continuing to disperse at 4500 rpm for 1 h, the zirconium oxide balls are filtered out to obtain an anti-ultraviolet aging thermal insulation slurry.
2. The method for preparing an anti-ultraviolet aging thermal insulation slurry according to claim 1, characterized in that: The acidic solution is any one of HCL, H2SO4, HNO3 or a mixture of several thereof.
3. The method for preparing an anti-ultraviolet aging thermal insulation slurry according to claim 1, characterized in that: The particle size of the nano CeO2 particles is 20-50 nm, the particle size of the fluorphlogopite particles is 1-3 μm, and the nano CeO2 particles and the fluorphlogopite particles are mixed at a mass ratio of 1:0.1-0.
5.
4. The method for preparing an anti-ultraviolet aging thermal insulation slurry according to claim 1, characterized in that: The particle size of the super hydrophobic SiO2 aerogel particles is 100-300nm.
5. The method for preparing an anti-ultraviolet aging thermal insulation slurry according to claim 1, characterized in that: The weight portion of the mixed powder is 5-20 parts, the weight portion of the superhydrophobic SiO2 aerogel is 5-20 parts, the weight portion of the silicone oil is 60-90 parts, and the weight portion of the dispersant is 1-5 parts.
6. The method for preparing an anti-ultraviolet aging thermal insulation slurry according to claim 1, characterized in that: The silicone oil is any one of dimethyl silicone oil, cyclopentadecane silicone oil or phenyl polytrimethicone silicone oil.
7. The method for preparing an anti-ultraviolet aging thermal insulation slurry according to claim 1, characterized in that: The dispersant is any one of PEG-10 polydimethylsiloxane, PEG-9 polydimethylsiloxyethyl polydimethylsiloxane, octyldodecanol stearoyloxystearate or PEG-11 methyl ether polydimethylsiloxane.
8. The method for preparing an anti-ultraviolet aging thermal insulation slurry according to claim 1, characterized in that: The particle size of the zirconia balls is 0.3 mm, and the weight of the added zirconia balls is 1.5 times the total weight of the dispersion slurry.